Methodological Approaches to~the Evaluation of~Innovation in~Polish and Ukrainian Regions, Taking into Account Digitalization - Olha Popelo; Svitlana Tulchynska; Alʹona Mykolaïvna Revko; Mykola P. Butko; Marta Derhaliuk (Comparative Economic Research. Central and Eastern Europe, 2022)
The article offers aqualimetric assessment of the innovation in regional economic systems, taking into account digitization. The study was based on the methodology of general scientific methods of cognition and special methods of scientific research in the field of the development of productive forces and regional economy. Namely, we used the dialectical method of scientific cognition to identify contradictions and interrelations of innovative development of the subjects of regional economic systems; analysis and synthesis to identify the mechanism for identifying and implementing priority areas of innovation in the regions; the grouping method for clustering regions according to the calculated values of the integrated index of innovation of the regions of Ukraine and Poland; statistical and economic-mathematical modeling for calculations and modeling of innovation of regions, and other methods.The calculations and analysis of the values of integrated indices of innovation activity in the regions of Ukraine and Poland are performed. These regions are grouped according to this indicator. The cartographic analysis is presented, and the region leaders, region outsiders, and regions with the average value of the integrated index of innovation are singled out. This study has theoretical and applied significance for the development of productive forces and regional economy as it provides for the development of a methodological approach to assessing the innovation activity of the regions of Ukraine and Poland, taking into account digitalization processes.
Keywords: B41; O3; O35; R1; 330; innovation; innovation activity; social innovation; infrastructure; modernization; digitization